Analysis of intracellular nucleotides by capillary electrophoresis-mass spectrometry - Friedecký, David; Bednář, Petr; Procházka, Martin; Adam, Tomáš (Nucleosides, nucleotides & nucleic acids, 2006)
A pilot study using capillary electrophoresis with mass spectrometry for the analysis of nucleotides in human erythrocytes is presented. Erythrocytes were incubated with 5-amino-4-imidazolecarboxamide riboside in order to mimic situation in defect of purine metabolism--AICA-ribosiduria. Characteristic AICA-ribotides together with normal nucleotides were separated by capillary electrophoresis in acetate buffer (20 mmol/L, pH 4.4) and identified on line by mass spectrometry.
Keywords: Ribonucleosides; Purines; erytrocyty; Hydrogen-Ion Concentration; ribonukleosidy; aminoimidazolkarboxamid; Aminoimidazole Carboxamide; Electrophoresis, Capillary; nukleotidy; Humans; elektroforéza kapilární; Mass Spectrometry; Nucleotides; puriny; koncentrace vodíkových iontů; Erythrocytes; lidé; hmotnostní spektrometrie